Aerogel Hybrids and Nanocomposites - Lázár, István; Menelaou, Melita (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint 'Aerogel Hybrids and Nanocomposites' is a collection of the latest publications in the research, development, and use of complex aerogel-based materials. The applications of aerogels in hard tissue engineering, new wound-healing materials to challenge bacterial infections, and the making of wearable aerogel fibers reveal their role and potential in the biomedical fields. Catalytic applications of aerogels are well demonstrated by the papers on environmental protection and green hydrogen production. The efficient removal of rare-earth ions, as well as the sensitization of their luminescence in aerogels, makes them environmentally and analytically valuable materials.